Leverage dan Partisipasi Ekspor: Studi Empiris pada Perusahaan Manufaktur di Indonesia - Perintis, Ilham; A.Panennungi, Maddaremmeng (Jurnal Kebijakan Ekonomi, 2019)
The study aims to investigate the relationship between leverage on firms' opportunities to participate in export markets at the levels of aggregate sectors and subsectors of manufacturing of Indonesia by using Industry Survey data published by Badan Pusat Statistik (BPS) for the period 2007 - 2015. The results of logistic estimation at the sectoral aggregate level indicate that the higher a firm has the financial capacity to meet obligations or that the company is not burdened by debt arising from the use of leverage, the firms are not financially constrained and have greater opportunity for firms to participate in the export market. In addition, at the manufacturing subsector level, opportunities for firms to enter the export market are different due to the heterogeneity on firms' characteristics from respective subsectors. Keywords: Export Participation, Leverage, Manufacturing subsectors, Indonesia